Innovative Strategies for Micro and Medium Enterprises Development by participation of PTkis in reducing the role of the Emok Bank in Kuningan Regency - Siti Komara (Eduvest - Journal of Universal Studies, 2024)
This research aims to analyze the activities "Emok Bank" viewed from sharia economic law and to formulate the innovative strategies in developing Micro and Medium Enterprises by involving the participation of Islamic colleges. The method used in this research is descriptive with a qualitative approach. The data analysis which is used in this study is the theory of Miles and Huberman to describe the results of study, while to analyze the relationship between the parties related to the development of UMKM (MSMEs) is by using TAWHIDI STRING RELATION theory and designing the innovative strategies using SWOT analysis. This study was conducted in Susukan village, Cipicung district, Kuningan Regency. It is one of the villages which gets the impacts of the activities of Emok Bank. The research results showed that the practices of borrowing borrowing which are held by Emok Bank have not been in accordance with the Sharia conomic law. The transaction parties have not could ensure yet to be able to manage his/her the property as well as not to BI checking and the loan feasibility. The borrowed money which is given by Bank EMok is not in the control of Emok Bank because of the government's property, the centered bank and even belonging to the investor. In the sharia economic law, the lent goods must be returned by the corresponding amount, while the loan at the Emok Bank is burdened interest even up to 25%.